National survey of training of psychiatrists on advance directives to refuse treatment in relation to bipolar disorder - Morriss, Richard; Mudigonda, Mohan; Bartlett, Peter; Chopra, Arun; Jones, Steven (Royal College of Psychiatrists, 2017)
Aims and Methods: To determine features associated with better perceived quality of training for psychiatrists on advance decision-making in the Mental Capacity Act (MCA), and whether the quality or amount of training were associated with positive attitudes or use of advance decisions to refuse treatment (ADRTs) by psychiatrists in people with bipolar disorder (BD). An anonymised national survey of 650 trainee and consultant psychiatrists in England and Wales was performed. Results: Good or better quality of training was associated with use of case summaries, role-play, ADRTs, assessment of mental capacity and its fluctuation. Good or better quality and two or more sessions MCA training were associated with more positive attitudes and reported use of ADRTs, although many psychiatrists would never discuss them clinically with people with BD. Clinical implications: Consistent delivery of better quality training is required for all psychiatrists to increase use of ADRTs in people with BD.